2022
DOI: 10.1007/s11102-022-01243-x
|View full text |Cite
|
Sign up to set email alerts
|

Pituitary stalk interruption syndrome: phenotype, predictors, and pathophysiology of perinatal events

Abstract: Purpose: There is limited data regarding Pituitary Stalk Interruption Syndrome (PSIS) from India. Moreover, the pathophysiological link between perinatal events and PSIS is unclear. We aim to elucidate the predictors of PSIS among patients with growth hormone de ciency (GHD) and perinatal events in PSIS by comparing cohorts of PSIS and genetically proven GHD without PSIS.Methods: Among 179 GHD patients, 56 PSIS and 70 genetically positive GHD (52-GHRHR, 15-POU1F1, and 3-PROP1) patients were included. Perinatal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 39 publications
3
9
0
2
Order By: Relevance
“…In the study group, we observed a signi cant male predominance in the CPHD-nonPROP1 group. This is consistent with observations of other authors describing similar cohorts (31).…”
Section: Discussionsupporting
confidence: 94%
“…In the study group, we observed a signi cant male predominance in the CPHD-nonPROP1 group. This is consistent with observations of other authors describing similar cohorts (31).…”
Section: Discussionsupporting
confidence: 94%
“…Among our patients with GH deficiency, TSH was the most common accompanying deficit, followed by ACTH, FSH/LH, and ADH. Remarkably, similar to a previously reported cohort of 56 patients with PSIS 15 , none of our patients with PSIS had ADH deficit.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to previous studies [14], the most prevalent cause of cCPHD in our cohort was PSIS. The high male-to-female ratio has been related to X-linked recessive genes and male susceptibility to prenatal and/or perinatal stresses [15]. The signs/complaints of short stature, followed by hypothyroidism, undescended testis/micropenis, hypoglycemia, delayed puberty, and polydipsia seen among our patients were also similar to previously reported commonly seen symptoms of prolonged jaundice, hypoglycemia, micropenis, or undescended testis in the newborn period and short stature or delayed puberty in childhood/adolescence [2,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These congenital disorders manifest as growth hormone deficiencies, lower body weights, and delayed growths in height, which is caused by pituitary dwarfism and the resulting deficiency in pituitary hormone release. While the underlying molecular mechanisms of these disorders remain unknown, it has been suggested that mutations in POU1F1, PROP1, and PTCH1 contribute to PSIS (Brauner et al, 2020;Diwaker et al, 2022). For the first time, our study provides functional evidence for the role of Robo1 deficiency as a cause for human disorders and presents a promising potential animal model.…”
Section: Discussionmentioning
confidence: 64%